2017
DOI: 10.1142/s0219633617500225
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic (MHD) stagnation point flow of Casson fluid over a stretched surface with homogeneous–heterogeneous reactions

Abstract: This article communicates the study of magnetohydrodynamic (MHD) stagnation point flow of Casson liquid towards a stretched surface. Chemical reaction model involving both heat and mass transfer is established. Effects of viscous dissipation and Joule heating are also considered. Appropriate transformations yield strong nonlinear ordinary differential system. The obtained nonlinear systems have been solved through built-in shooting method. Velocity field shows decreasing behavior for higher estimation of magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Moreover, they discussed over a stretched surface, transfer of heat in magnetohydrodynamic (MHD), and stagnation point flow of Cross fluid. Khan et al 5 worked on transformation of heat in MHD numerically simulation. Mehwish et al 6 showed her work on convection of heat transfer in a cross fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they discussed over a stretched surface, transfer of heat in magnetohydrodynamic (MHD), and stagnation point flow of Cross fluid. Khan et al 5 worked on transformation of heat in MHD numerically simulation. Mehwish et al 6 showed her work on convection of heat transfer in a cross fluid.…”
Section: Introductionmentioning
confidence: 99%
“…In the last couple of decades, engineers and researchers have been carried out examinations on the important characteristics of fluid flow and heat transfer subject to various assumptions. Combustion problems have been widely studied in a radiated flow towards a stretched and flat surface by numerous analysts 16–29 …”
Section: Introductionmentioning
confidence: 99%
“…Combustion problems have been widely studied in a radiated flow towards a stretched and flat surface by numerous analysts. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] The present communication, therefore, aims to scrutinize and thus provide awareness on how entropy optimization in radiated flow towards a flat surface of sheet is affected due to variables, that is, magnetic parameter, Darcy-Forchheimer number and radiation parameter, and the type of flow. It is trusted that this would prompt expanded understanding in the current knowledge of heat transport and entropy generation minimization and allow engineers and researchers to design such types of mathematical modeling that not only accomplishes the desired objective in term of heat transport and entropy generation minimization.…”
Section: Introductionmentioning
confidence: 99%
“…Hayat et al [ 39 ] studied the impact of homogenous-heterogeneous reactions in boundary layer flow of nanofluid saturating porous medium in presence of melting heat transfer. Few studies on heat and mass transfer can be found through the refs [ 40 43 ].…”
Section: : Introductionmentioning
confidence: 99%